Smart Health Internet of Thing for Continuous Glucose Monitoring: a Survey - Yusuf, Nuhu; Hamza, Aminu; Muhammad, Rilwan Sabo; Aminu Suleiman, Maryam; Abubakar, Zainab Aminu (International Journal of Integrated Engineering, 2020)
Health monitoring system allows patients to monitor the health-related problem to avoid further complications which could result in loss of life. Smart health is one of the categories of a health monitoring system that uses Smartphone’s and sensors to effectively monitor patient health status. However, the smart health internet of thing methods for glucose monitoring still does not provide accurate glucose reading. Hence, diabetes patient can easily loss life. To help understand this challenge, a comprehensive survey focused on smart health internet of thing methods for continuous glucose monitoring was conducted. The paper discusses the benefit and challenge of each method applicable to glucose monitoring. It was observed that several smart health methods required sensor to function. Smart vehicles and remote monitoring have less attention. However, when accommodates can provide future opportunities.